Tax revolts and sovereign defaults - Fernando Arce; Jan Morgan; Nicolas Werquin (Federal Reserve Bank of Chicago, 2024)
Protests and fiscal crises often coincide, with complex causal dynamics at play. We examine the interaction between tax revolts and sovereign risk using a quantitative structural model calibrated to Argentina during the Macri administration (2015-2019). In the model, the government can be controlled by political parties with different preferences for redistribution. Households may opt to revolt in response to the fiscal policies of the ruler. While revolts entail economic costs, they also increase the likelihood of political turnover. Our model mirrors the data by generating political crises concurrent with fiscal turmoil. We find that left-leaning parties are more prone to default, while right-leaning parties sustain higher debt levels. Revolts impact default risk through two channels. First, political crises can increase sovereign risk by facilitating transitions from right-wing to left-wing administrations that culminate in default. Second, the threat of frequent revolts during default periods can deter the government and increase commitment. In our calibration, the latter channel dominates the former with revolts operating as an endogenous default cost. Relative to a model without revolts, our framework can sustain higher levels of debt and reduce the frequency of defaults.
Keywords: E32; E44; F41; G01; G28; 330; Civil unrest; financial crises; sovereign default; redistribution